Carbon Transfer Efficiency and Risk of Fisheries Collapse in Three Large Marine Ecosystems Around China - Chen, Dongxing; Wang, Xutao; Hou, Minchi; Wang, Qiabin; Liu, Qianqian; Huang, He; Zhang, Yafeng (Frontiers in Marine Science, 2022)
Fisheries catch is determined by a complex combination of biological and industrial factors. In this study, using data from the online database Sea Around Us from 1950 to 2018, the risk of fisheries collapse was assessed for the three large marine ecosystems (LMEs) around China by analyzing the carbon transfer efficiency, mean trophic level, and mean maximum length of fisheries catch and expansion factor. In addition, these were compared with the corresponding values for other LMEs, especially the Humboldt Current and the North Sea LMEs, which experienced fisheries collapse. Our results revealed high carbon transfer efficiencies in LMEs around China, suggesting large fishing efforts compared with LMEs with similar primary production. Although marine fish landings did not decline significantly, they were maintained by potential resources associated with offshore and deep expansion and fishing of lower–trophic-level species and juvenile fish. However, the potential resources have been largely consumed in the East China Sea and South China Sea LMEs, where the ratio of the primary production required to sustain catches to the total primary production (%PPR) was greater than 50%. In contrast, this ratio in the Yellow Sea LME was lower; however, this value was still higher than the sustainable ratio in the Humboldt Current LME. Without proper fisheries management, the three fisheries around China are likely to collapse, as observed in case of the North Sea LME in the 1970s.